Semiotika Pesan Akhlak dalam Film Pendek Kaya Tanpa Harta - Fitriany, Sarah; Azizi, Muhammad Hildan (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2021)
This study attempts to examine the meaning of the moral message embedded within the signs in the short film Kaya Tanpa Harta. Through the qualitative method and the semiotic approach of Roland Barthes, this study has found that the moral messages contained in this film texts are requiring muslims to be patient when experiencing economic problems and to do halal job even though in the low-wage workforce as well. In addition, the film texts also have conveyed message related to caring for and help one another as well as repent when one makes a mistake. Such moral messages are conveyed through depcition of the characters in a binary opposition with other characters, such as a strong young man who despairs and robs compared to an old mother who is passionate about work and continues to give alms.